Antifungal susceptibility of malassezia furfur, malassezia sympodialis and malassezia globosa to azole drugs and amphotericin B evaluated using a broth microdilution method - Rojas, Florencia Dinorah (2014)
We studied the in vitro activity of fluconazole (FCZ), ketoconazole (KTZ), miconazole (MCZ), voriconazole (VCZ), itraconazole (ITZ) and amphotericin B (AMB) against the three major pathogenic Malassezia species, M. globosa, M. sympodialis, andM. furfur. Antifungal susceptibilities were determined using the broth microdilution method in accordance with Clinical and Laboratory Standards Institute reference document M27-A3. To support lipid-dependent yeast development, glucose, peptone, ox bile,malt extract, glycerol, and Tween supplements were added to Roswell Park Memorial Institute RPMI 1640 medium. The supplemented medium allowed good growth of all three species studied. The minimal inhibitory concentrations (MICs) were recorded after 72 h of incubation at 32oC. The three species showed different susceptibility profiles for the drugs tested. Malassezia sympodialis was the most susceptible and M. furfur the least susceptible species. KTZ, ITZ, and VCZ were the most active drugs, showing low variability among isolates of the same species. FCZ, MCZ, and AMB showed high MICs and wide MIC ranges. Differences observed emphasize the need to accurately identify and evaluate antifungal susceptibility of Malassezia species. Further investigations and collaborative studies are essential for correlating in vitro results with clinical outcomes since the existing limited data do not allow definitive conclusions.